Aligning with complexity: system-theoretical principles for research on differentiated instruction - Wouter Smets; Katrien Struyven (EARLI, 2018)
Much scholarly research was dedicated over the last years to address the difficult task of responding adequately to student differences. Differentiated instruction is a teaching philosophy and practice that deals with this ambitious target. The aim of this paper is to reflect on how system theory  methodologically challenges research on differentiated instruction. Based on these insights which are only recently applied in educational sciences it is documented how current research on differentiated instruction does not yet mirror the full complexity of the concept of differentiated instruction. Three challenges for research on differentiated instruction are presented: to focus on the interplay between micro- an meso-level interaction; to acknowledge for external influences in research design; and, to use patterns of non-linear causality. Three design principles for research on differentiated instruction are presented to cope with these challenges: organic design, interactionality and reflectivity. By using these principles we believe research on differentiated instruction would be more aligned with the theoretical foundations of the concept.